Climate Change Policy and Practice - Friis-Hansen, Esbern; Aben, Charles; Okiror, John James; Bashaasha, Bernard; Suubi, Godfrey (Danish Institute for International Studies, 2015)
This section first analyses the national policy response and characterizes the new climate change policy arena as compared with the more established disaster and emergency response policies. Thereafter the institutional landscape involved with climate change is mapped. This is followed by an assessment of the relationship between national policy and local government practice by introducing the principle of subsidiarity. Finally, we discuss how climate change is articulated or ignored among local government politicians, exemplified by a case study from Amuria District, where climate change was successfully used as a platform for local government elections in 2006.